Principal’s Supervision Strategy to Improve Teachers’ Performance Based on Professional Competence - Hasanah, Cucun; Sururi, Sururi (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2025)
This study aims to examine the supervision strategies implemented by the principal in improving teacher performance based on professional competence at SD N Sukasenang 2, Garut. The approach used is descriptive qualitative with a case study method. Data were obtained through in-depth interviews, participatory observation, and analysis of school documents. This study identified the stages of supervision that include planning, implementation, and evaluation, which are carried out systematically and continuously. The results of the study indicate that the principal utilizes a clinical supervision approach, professional training, and personal coaching to improve pedagogical competence and teacher professional abilities. This strategy is considered effective in improving teacher performance, especially in terms of lesson planning, implementing innovative methods, and assessing learning outcomes. However, several obstacles were detected, such as the principal’s limited time, variability in teacher competency levels, and lack of facility support. To overcome these challenges, the principal developed a collaborative approach by involving senior teachers and forming a teacher working group. This study recommends increasing the intensity of supervision, providing adequate resources, and strengthening the culture of reflection in learning to support continuous teacher professional development. These findings are expected to be a reference in developing supervision strategies in other elementary schools.